DEVELOPMENT OF NATIONAL EDUCATION OF UNIVERSITY STUDENTS THROUGH MEDIA TECHNOLOGIES. (Conferencea, 2022)
The article acknowledges that success in the development of national education of students can be achieved only through the effective use of media technology. As noted in the article, a creative environment and advanced pedagogical experience play a special role in the development of creative abilities in students. In our study, a statistical analysis of the results obtained at the initial and final stages is presented. The experiment presents tables consisting of test results and statistical calculations.